Kajian Teori Pluralisme Hukum terhadap Sistem Hukum di Aceh - Hairun Tri Wahyuni Sagala (INTERDISCIPLINARY JOURNAL ON LAW, SOCIAL SCIENCES AND HUMANITIES, 2022)
Abstract Legal pluralism is not a new concept that has emerged in the modern legal system, but an approach to analyzing the operation of various legal systems side by side in the system of government of a nation-state. Aceh is one of the provinces in Indonesia which has several legal systems. The province of Aceh is viewed as a province that has special autonomy status with a multicultural pattern, because of the plurality of regulatory systems in its society. The pluralism (pluralism) of the legal system in Aceh arises because of ethnic diversity and the application of Islamic religious values ​​to every aspect of Acehnese life, especially in the field of upholding the legal system itself. The diversity (Pluralism) of the legal system that lives and applies in Aceh has the power of law and recognition from the Indonesian government with the passing of Law number 11 of 2006 concerning the Governance of Aceh, so in addition to the enactment of the state legal system (state law), de facto in Aceh to the legal system of procedures (adat law) applies, and the system of religious rules / Islamic law (religious law / Islamic law). The research method used is juridical sociology. The data were analyzed using a qualitative descriptive approach. Keywords: Legal Pluralism, Legal System of Aceh, Islamic Law